2009
DOI: 10.1038/laban0509-161
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey to evaluate contemporary prevalence of viral agents and Mycoplasma pulmonis in laboratory mice and rats in western Europe

Abstract: To evaluate current prevalence rates of 24 viruses and of the bacterium Mycoplasma pulmonis, the authors retrospectively surveyed serological data obtained from laboratory mice and rats housed in more than 100 western European institutions. Serum samples were submitted to the authors' institution for testing between January 2007 and June 2008. The prevalence of an infection was defined as the percentage of tested samples that yielded positive results for a specific agent. In mice, the most commonly detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 13 publications
1
60
0
4
Order By: Relevance
“…In this study, we demonstrated that the prevalence of MNV was higher than those of MHV and M. pulmonis, which was consistent with serological survey data that indicates that MNV is the most prevalent viral pathogen in contemporary mouse colonies [13,15]. We found that some serum samples were negative for antibodies to MHV and M. pulmonis but positive for antibody to MNV-S7.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we demonstrated that the prevalence of MNV was higher than those of MHV and M. pulmonis, which was consistent with serological survey data that indicates that MNV is the most prevalent viral pathogen in contemporary mouse colonies [13,15]. We found that some serum samples were negative for antibodies to MHV and M. pulmonis but positive for antibody to MNV-S7.…”
Section: Discussionsupporting
confidence: 90%
“…The results suggest that MNV infection is more prevalent than mouse hepatitis virus (MHV) and Mycoplasma pulmonis (M. pulmonis) infections in conventional mouse colonies in Japan, as is the case in other areas of the world [13,15].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prevalence data may be helpful in deciding which agents to monitor. [18][19][20][21][22][23][24] Local prevalence of an infectious agent may also depend on numerous other factors, such as the strain, immune status, age and sex of the animals, and the local conditions in each unit, such as open cages or microisolation cages, intensity of animal movement within and between facilities, and working routines.…”
Section: Prevalence Of Infectious Agentsmentioning
confidence: 99%
“…17,18 This higher rate of MPV infection in Taiwan could result from a lack of routine monitoring for MPV before 2008 and difficulties in the complete elimination of infected transgenic colonies since that time.…”
Section: Discussionmentioning
confidence: 99%